CHEMICAL REACTIONS AND BIOLOGICAL ACTIVITY OF CARBAMATE DERIVATIVES - Soibova F.S.,Khatamova M.S., Mustafayeva S.U. (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Currently, satisfying the needs of the national economy for bioactive substances and searching for new compounds, developing and implementing the technology for their production are among the urgent tasks facing the chemical science. In this article, the methods of synthesis of new bioactive substances based on the chemical reactions of hexamethylene bis-[(alkyl)-carbamate] and the reaction of substances with biological activity, diisocyanates with aliphatic alcohols, creation of a harmless and waste-free technology for their production, and the search for biostimulants among the obtained substances and methods of implementation were thoroughly studied.